Mi'kmaw Catholicism: oral tradition, transculturation, and resistance in Mi'kma'ki - Hughes, M.I. Micheline (2023)
The Mi’kmaw Nation has lived in Mi’kma’ki for at least 11,000 years. In the time of early colonial efforts in Turtle Island, the Mi’kmaq submitted Catholicism to processes of transculturation which allowed it to be meaningful and beneficial to them. The decision to adopt and adapt Catholicism was validated by the oral traditions of the Mi’kmaq. Since this time, Mi’kmaw stories have come to reflect the various ways that Mi’kmaw Catholicism is understood, practiced, and valued by this Nation. This dissertation employs Mi’kmaw stories primarily from the mid-to-late 1800s to investigate Mi’kmaw Catholicism. Indigenous methodologies are the foundation of this work. Postcolonial theory and story as theory are used to understand the Mi’kmaq’s perspectives of their religious tradition as well as the role that story played in its process of transculturation. Relationships between story and the uptake of Catholicism, Mi’kmaw identity, agency, resistance, and imagining a path to a just reality are explored. I believe that telling stories that incorporate Mi’kmaw Catholicism was a way to express the lived realities of the Mi’kmaq; a way to preserve voice and resist erasure. It seems that stories provided a location for the transculturation of Catholicism to occur, bringing both Mi’kmaq and Catholic actors into conversation with each other. Ultimately, I believe that stories allowed the Mi’kmaq to imagine a reality in which their religion, their families, and msit no’kmaq, all my relations, flourished. February 2024 Congress Graduate Merit Award (2020). C. D. Howe Memorial Foundation Fellowship in Creative Writing and Oral Culture, University of Manitoba (2019; 2016). Raymond F. Currie Fellowship, University of Manitoba (2017). J.G. Fletcher Award, University of Manitoba (2017). President’s Graduate Scholarship for First Nations, Inuit and Métis Students, University of Manitoba (2015). University of Manitoba Graduate Fellowship, University of Manitoba (2015).